Allergy – Patients with Atopic Dermatitis Express Themselves Through a Questionnaire - Shourick J; Taïeb C; Seite S (Dove Medical Press, 2021)
Jason Shourick,1 Charles Taïeb,2 Sophie Seite3 1Département Epidémiologie, Hôpital de Toulouse, Toulouse, France; 2Patients Priority Department, European Market Maintenance Assessment, Fontenay Sous-bois, France; 3La Roche-Posay Dermatological Laboratories, Levallois Perret, FranceCorrespondence: Charles TaïebPatients Priority Department, European Market Maintenance Assessment, Fontenay Sous-bois, FranceTel +00 33 771772100Email charles.taieb@emma.clinicIntroduction: Allergies are becoming more prevalent across the globe and can be linked to several skin diseases, particularly atopic dermatitis (AD). Disruption of the immune system in the skin can lead to inflammatory diseases such as atopic and contact dermatitis, skin infections, and allergies. This is especially evident in processes such as “atopic march”, where in childhood, the development of atopic dermatitis can later lead to food allergies, allergic rhinitis and asthma.Objective: The aim of this international online survey is to study the link between self-reported doctor-diagnosed AD and allergy prevalence.Methodology: Our survey queried a representative sample of the general population over the age of 18 from five countries (Brazil, China, Russia, the USA and France).Results: A total of 9399 participants answered the entire online questionnaire. Among them, 2483 (26.4%) had an allergy diagnosed by a doctor (1243 with food allergies (13.2%), 1564 with respiratory allergies (16.6%) and 1669 with skin allergies (17.7%)). There were 794 (31.9%) participants with current AD in the allergy group and 640 (9.25%) in the group without allergies (p< 0.001), and there were 1299 (52.3%) participants with CAD in the allergy group versus 1368 (19.8%) in the group without allergies (p< 0.001). Multivariate analysis showed ORs of 3.24 [2.98, 3.63] (p< 0.001) for current AD and 2.4 [2.09, 2.74] (p< 0.001) for CAD. There was no significant interaction between AD and CAD (p=0.6).Conclusion: A total of 26.4% of survey respondents reported having doctor-diagnosed allergies. Among these patients, half reported having AD during childhood, and 1/3 reported having a current AD. CAD and AD patients clearly have a higher risk of having an allergy than patients without CAD or AD.Keywords: allergy, atopic dermatitis, patient centricity